Село, крестьяне и аграрная реформа: украинский вариант - Иваненко, Е. (Социология: теория, методы, маркетинг, 2007)
The article concerns agrarian reform (its final stage) as a component of the transformational processes, taking place in Ukraine, as well as a tool for intervention of the social technologist/social engineer (legislative/executive power) in agricultural production and activity of village and villagers.The nature of this reform and its destructive character are exemplified in results of different sociological surveys of the rural population of Ukraine. Besides, one cannot but mention numerous moral and psychological problems caused by unemployment, non-payment of wage, impoverishment of peasants, extinction of village, and other negative aspects of the mentioned above transformations.